2021
DOI: 10.3389/fimmu.2021.789914
|View full text |Cite
|
Sign up to set email alerts
|

m6A Regulator-Mediated Methylation Modification Patterns and Tumor Microenvironment Infiltration Characterization in Acute Myeloid Leukemia

Abstract: Recent studies have demonstrated epigenetic regulation of immune responses. Nevertheless, the underlying effect of RNA N6-methyladenosine (m6A) modifications on tumor microenvironment cell infiltration remains elusive. In this study, we thoroughly assessed m6A modification patterns of 255 myeloid leukemia specimens based on 23 m6A regulators. Consensus clustering of the 23 m6A regulators was performed to determine three distinct m6A modification patterns that were remarkably consistent with three immunophenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…m6A, a widely studied form of RNA methylation modification, is essential for regulating RNA transcription, processing and translation, which in turn affects cellular metabolic activities. Different m6A modification patterns are known to interact with the immune phenotypes of tumors, including immune rejection, immune activation, and immune inertness, thus, estimating the m6A pattern of a tumor might enable the characterization of TME infiltration and provide guidance for improved immunotherapy strategies ( Du et al, 2021 ; Zhang et al, 2020b ). In the present study, we analyzed the correlation between m6A and m7G regulators using a deconvolution algorithm and found that most of the genes in the two groups showed a positive correlation with each other.…”
Section: Discussionmentioning
confidence: 99%
“…m6A, a widely studied form of RNA methylation modification, is essential for regulating RNA transcription, processing and translation, which in turn affects cellular metabolic activities. Different m6A modification patterns are known to interact with the immune phenotypes of tumors, including immune rejection, immune activation, and immune inertness, thus, estimating the m6A pattern of a tumor might enable the characterization of TME infiltration and provide guidance for improved immunotherapy strategies ( Du et al, 2021 ; Zhang et al, 2020b ). In the present study, we analyzed the correlation between m6A and m7G regulators using a deconvolution algorithm and found that most of the genes in the two groups showed a positive correlation with each other.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, the three m6A clusters (writers, erasers and readers) are correlated with subsets of the infiltrating immune landscape, including activated CD8+ T cells, NK cells, activated DCs, macrophages and Treg cells. The low m6Ascore contributes to the increased mutation burden, immune activation and survival rates and is associated with an enhanced response to anti-PD-1/PD-L1 immunotherapy (139)(140)(141). In bladder cancer, 9 m6A-related lncRNAs were dramatically associated with overall survival outcomes of bladder cancer.…”
Section: M6a Functions In Shaping the Local Immune Microenvironmentmentioning
confidence: 99%
“…With the breakthroughs in the identification and understanding of m6A writers, erasers and readers, m6A methylation has been shown to affect virtually every aspect of RNA metabolism, including RNA expression, translation, splicing, decay, nuclear export, and RNA-protein interactions ( 60 , 61 ). Recently, there is growing evidence that writers, erasers and readers of m6A RNA modifications are related to multiple types of human cancers, including: gastric cancer (GC) ( 62 ), colorectal cancer (CRC) ( 63 ), breast cancer (BC) ( 64 ), lung cancer (LC) ( 65 ), hepatocellular carcinoma (HCC) ( 66 ), pancreatic cancer (PC) ( 67 ), prostate cancer (PCa) ( 68 ), acute myeloid leukemia (AML) ( 69 ), cervical cancer (CC) ( 70 ) ovarian ( 71 ) and endometrial cancer ( 72 ) (OC and EC), etc. m6A RNA methylation plays an important role in promoting CSC self-renewal, proliferation and resistance of cancer cell to radiation or chemotherapy.…”
Section: M6a Modification and Solid Tumorsmentioning
confidence: 99%